INVENTING URBANITY: URBAN MOVEMENTS IN POLAND - KUBICKI, PAWEŁ (Society Register, 2020)
The article discusses the process of formation and transformation of urban movements in Poland. Conclusions are based on the data collected during the research project “Urban Social Movements in Poland” supported by the National Science Centre. For the requirements of the project was adopted a method of qualitative research using the techniques of in-depth narrative interviews, participant observations and secondary data analysis. The author conducted 30 in-depth interviews with leaders of urban movements from sixteen cities. The article describes the process of structuralization and the creation of the identity of the Polish urban movement and their role on the local political stage, stressing, in particular, their significant role as creators of a new discourse in Polish cities.